Evolution of Credit Risk Management Capability Maturity: Lessons from the Indian Banking Sector. (December 2014) - Arora, Anju; Kumar, Muneesh
A wide array of credit risk management (CRM) practices have been followed by commercial banks since their inception. These practices have evolved over the years; new practices/strategies have been formulated, old practices have been updated/revised, traditional operations are being replaced by new sophisticated procedures. With such continuous evolution of CRM practices, CRM capability maturity of banks has also improved over time. Further, the role/importance and effectiveness of each CRM practice in determining the maturity of CRM capability is an important issue that needs to be addressed. A number of capability maturity models have been suggested in general for a business organisation. However, these studies focus on the assessment of overall business risk management maturity and do not offer any model to trace the path of evolution towards maturity in CRM capability in commercial banks. This article attempts to fill this gap by investigating into how commercial banks mature in their ability to manage credit risk in their advances portfolio. The objective of this study is to go beyond descriptive in terms of specifying practices, challenges and issues in each stage of CRM capability maturity and also be prescriptive in terms of recommended strategies and actions to move on to the next higher level of CRM capability maturity. The path of evolution of credit risk management capability maturity is illustrated on the basis of primary data collected from 35 Indian commercial banks (representing 70 per cent of the population) through a structured questionnaire in year 2007–2008. A comprehensive list of questions relating to major elements of CRM namely, ( a ) CRM organisation, ( b ) CRM policy and strategy; and ( c ) CRM operations and systems at the transaction level; and ( d ) CRM operations and systems at the portfolio level were included in questionnaire. The CRM index tool is employed to benchmark a given commercial bank's approach to CRM against four standard levels of maturity. The statistical analysis of scores in four major elements of the CRM index for banks lying in different stages of maturity clearly brings out whether or not credit risk processes/techniques/tools/procedures are adequate, identifies realistic targets for improvement and shall enable bank management to frame concrete plans for evolving towards a higher CRM capability maturity level. This study, by drawing conclusions from empirical data, is unique and contributes to additional insights into the risk management literature in emerging economies.